2020
DOI: 10.1186/s12879-020-05551-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection in first trimester of pregnancy marked by a liver cytolysis in a woman previously treated by hydroxychloroquine for repeated implantation failure: a case report

Abstract: Background In December 2019, a new disease (COVID-19) caused by a novel coronavirus called SARS-CoV-2 emerged in China and spread to many other countries. There is only limited data about the clinical features of COVID-19 during pregnancy, especially in first trimester. Case presentation We report a COVID-19 infection in a 35 years-old patient in first trimester of pregnancy and its consequent medical care. At 7 weeks of pregnancy, the patient, who did not have any pregestational comorbidities, complained of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Only a portion of the studies (9) reported some sort of complication during the span of pregnancy which pertained to 15 patients [ 22 27 , 37 , 39 , 40 ]. Disseminated intravascular coagulation (DIC) (20%; 3/15), preeclampsia (13%; 2/15), as well as liver cytolysis, chorioamnionitis, ARDS, hyperemesis gravidarum, pneumothorax and gestational diabetes (each observed in 1/15 of the reported patients) were the most commonly observed complications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a portion of the studies (9) reported some sort of complication during the span of pregnancy which pertained to 15 patients [ 22 27 , 37 , 39 , 40 ]. Disseminated intravascular coagulation (DIC) (20%; 3/15), preeclampsia (13%; 2/15), as well as liver cytolysis, chorioamnionitis, ARDS, hyperemesis gravidarum, pneumothorax and gestational diabetes (each observed in 1/15 of the reported patients) were the most commonly observed complications.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 223 neonates, the outcomes of 60 infants (31/60: maternal infection during 1 st trimester and 29/60: 2 nd trimester infections) from 20 studies were specified as deceased/terminated, miscarriage, alive/delivered, or still ongoing pregnancy [ 17 , 22 33 , 36 , 37 , 39 43 ]. While the majority of 1 st trimester infection neonates had a reported status of ongoing pregnancy ( n = 24/31: 77.4%), 4/31 (12.9%) reported miscarriages, 1/31 (3.2%) abortion, 1 (3.2%) stillbirth and 1 (3.2%) chemical pregnancy were also noted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, due to the virus's novelty and recent spread, there is a scarcity of data on maternal and perinatal outcomes when the infection occurs in the early trimester of pregnancy. The CDC's frequent report emphasized adverse effects of COVID-19 on pregnancy and prevails on more extensive research to be carried out [14]. Evaluating the liaison of the early gestational trimesters of pregnancy is critical in COVID-19 for an effective counseling and provides vital intuition into pandemic may influence the future pregnancy.…”
Section: Introductionmentioning
confidence: 99%